2003
DOI: 10.1097/00054725-200301000-00001
|View full text |Cite
|
Sign up to set email alerts
|

A Population- and Family-Based Study of Canadian Families Reveals Association of HLA DRB1*0103 With Colonic Involvement in Inflammatory Bowel Disease

Abstract: The aim of this study was to identify major histocompatibility complex alleles associated with the development and clinical features of inflammatory bowel disease (IBD). Genotyping at the human leukocyte antigen (HLA) DRB1 and DQB1 loci was performed on individuals from 118 Caucasian IBD sibling pair families and on 216 healthy controls. Both population- and family-based association tests were used to analyze data obtained on the entire study population and on clinical subgroups stratified by diagnosis, ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 47 publications
5
44
0
1
Order By: Relevance
“…29,32,35,36,66 -68 Previous studies have indicated that the association is very strong among patients with severe or extensive disease, 35,36,65,66,69 and the same allele has subsequently been linked to CD with colonic location. [32][33][34] In the present study we were able to confirm the association of the HLA-DRB1*0103 allele with UC, and a similar trend was present in CD. In addition, HLA-DRB1*0103-positive UC patients had more often extensive inflammation as well as severe disease as defined by need of colectomy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…29,32,35,36,66 -68 Previous studies have indicated that the association is very strong among patients with severe or extensive disease, 35,36,65,66,69 and the same allele has subsequently been linked to CD with colonic location. [32][33][34] In the present study we were able to confirm the association of the HLA-DRB1*0103 allele with UC, and a similar trend was present in CD. In addition, HLA-DRB1*0103-positive UC patients had more often extensive inflammation as well as severe disease as defined by need of colectomy.…”
Section: Discussionsupporting
confidence: 84%
“…30,31 HLA-DRB1*0103 association has been reported both with colonic CD and with severe, extensive UC. [32][33][34][35][36] Recent genome-wide association (GWA) studies in CD have revealed new insights into the genetics of IBD. [37][38][39][40][41] The study by Duerr et al 37 reported significant association of IBD with the IL23R gene.…”
mentioning
confidence: 99%
“…Replicated HLA class Ⅱ associations in IBD include HLA-DRB1*1502 (serological marker HLA-DR2) [76] association with UC, and HLA-DRB1*0103 association with UC and colonic CD [77,78] . HLA-DRB1*0103 is noteworthy in that it is a risk factor for both UC and colonic CD, suggesting it may play a role in chronic inflammation of the colon independent of major IBD phenotype (i.e., CD or UC) [78] .…”
Section: Hla Associationsmentioning
confidence: 99%
“…HLA-DRB1*0103 is noteworthy in that it is a risk factor for both UC and colonic CD, suggesting it may play a role in chronic inflammation of the colon independent of major IBD phenotype (i.e., CD or UC) [78] . As with IBD5, the DRB1*0103 and DRB1*1502 class Ⅱ variants are in strong linkage disequilibrium with SNPs on multiple immunologically active candidate genes.…”
Section: Hla Associationsmentioning
confidence: 99%
“…43 Genetics appears to play a role in disease location, as well as in the development of EIMs and some genetic variants that are associated with colonic involvement in CD may also increase the risk of PA. For example, HLA DRB1*0103 allele carriage is much more common among CD patients with colonic disease than among healthy controls, indicating that this allele may be associated with both CD risk and disease location. 44,45 Furthermore, HLA DRB1*0103 has been associated with Type I peripheral arthritis, a migratory pauciarticular large joint arthritis. 13 This published study was performed in a pooled UC and CD cohort without including location of the disease as an independent variable, thus, this association between colonic involvement and genotype could not be assessed.…”
Section: Discussionmentioning
confidence: 99%